DEVELOPMENT OF ARTERIAL VESSELS OF THE STOMACH IN THE LATE FETAL PERIOD OF HUMAN ONTOGENESIS AND IN NEWBORNS - Loytra, A.O.; Shkrobanets, A.A.; Boichuk, O.M.; Lopushniak, L.Ya.; Dmytrenko, R.R.; Rusnak, V.F.; Halahdyna, A.A. (World of Medicine and Biology, 2019)
During the 7-8th month of the fetal period, the left gastric artery in all cases was the first branch that arose from the abdominal trunk. At the level of the cardiac region of the stomach, it was divided into 2 branches – the anterior and posterior in 14 cases (out of 15 examined), and in 1 case into 3 branches – anterior, middle and posterior. The right gastric artery was a branch of the common hepatic artery in 5 cases, in 8 instances it was hepatic and in 2 – of the left side of the latter. In 11 cases, it is represented by one trunk and forms an anastomosis with the anterior branch of the left gastric artery by direct connection, or by means of lateral branches. The vessels of the stomach of the 9-10-month-old fetuses are studied on 10 objects. The left gastric artery in 9 cases is divided into the anterior and posterior branches, and in one case it is represented by one trunk. The right gastric artery in 6 cases is a branch of the hepatic artery, in 4 cases – of the common one. In 7 observations, the artery is divided into 2 branches (the anterior and posterior), which are anastomosed with the corresponding branches of the left gastric one. Stomach vessels of newborns have been studied on 5 objects. The left gastric artery in all cases is divided into the anterior and posterior branches. The right gastric artery arose from the hepatic one and in all cases is represented by one vessel, which, either directly or by secondary branches, is anastomosed with the anterior branch of the left gastric artery.